Mekanisme Penyelidikan, Penyidikan Dan Mengadili Di Indonesia Pasca Orde Baru - Diah Resti Vilani; Niken Kurnia Yunita; Ahmat Luqman Nanda; David Aldo Wijaya (Pusat Riset dan Inovasi Nasional, 2023)
Inquiry and investigation in the mechanism there is a difference between the two. Article 1 point 5 of the Criminal Procedure Code regulates investigations to determine whether an event that is suspected of being a crime is true before finally proceeding to the level of investigation. Where the investigation stage aims to determine the truth of a criminal act. After finding out who the perpetrators of the crime were, then in accordance with the constitution a court process will be carried out through an independent judicial power. Merdeka has the principle that judicial power must be free from any form of encouragement or interference from any outside party. It is different from the power to adjudicate in the post-New Order era where legal dualism occurred. This study uses a normative juridical method with a statutory approach (Statute Approach) regarding Law Number 14 of 1970 concerning Judicial Power in the New Order regime as well as a Case Approach (Case Approach) of legal dualism carried out by President Soeharto where presidential power is attached to legal authority. justice. The power of the president attached to the power of the judiciary will give birth to the independence or independence of the decisions of the judges because there is interference from the power of the president.